Interfacial formation of intermetallic Ni-Al-Ti systems formed by induction heating - Riyadi, Tri Widodo Besar; Siswanto, Waluyo Adi; Zhu, Xiaomeng (Frontiers in Mechanical Engineering, 2022)
Intermetallic systems of Ni, Al, and Ti are candidates for lightweight materials that offer high temperature resistance. Combustion synthesis has been widely studied to produce intermetallic and coating deposition by exploiting the heat released by the combustion. An underlayer is often used to enhance the adhesion of the coating to the substrate. The interaction of the coating and the underlayer during heating is therefore crucial for achieving a good quality of adhesion. The objective of this work was to investigate the microstructure and properties of the interfacial formation across the NiAl coatings and Ti underlayers formed by combustion synthesis. Induction heating was used to initiate the heating and reaction of the reaction process with different heating rates. The microstructure was characterized by SEM and EDX, whereas the formed phases were identified using XRD tests. The hardness distribution was measured by the Vickers microhardness test. The result shows that NiAl with Al-rich and Ni-rich were formed in the coating region. The microstructure observed in the underlayer confirms the formation of the several intermetallic phases of Ni-Ti and Ti-Al systems. The infiltration of Ni and Al elements from Ni and Al to Ti sides was responsible for generating a reaction between Ni-Ai-Ti. The hardness distribution along the coating and underlayer was measured to support the properties of the formed phases. This work improves the understanding of second reactions across the interface during the fabrication of coatings that apply an underlayer.